2019
DOI: 10.2147/idr.s228612
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative Study Of Genetic Diversity, Virulence Genotype, Biofilm Formation And Antimicrobial Resistance Of Uropathogenic <em>Escherichia coli</em> (UPEC) Isolated From Nosocomial And Community Acquired Urinary Tract Infections</p>

Abstract: IntroductionEscherichia coli is a Gram-negative opportunistic human pathogen, which has aroused considerable medical interest for being involved in cases of urinary tract infection.AimCharacterize the E. coli isolated both in the hospital and in the community.MethodologyA total of 200 E. coli isolated in urine samples from hospital and community were evaluated in biofilm formation assay and hydrophobicity MATS method. Antimicrobial susceptibility was performed through agar-diffusion technique. Virulence and ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In contrast, the substantial number of the 50 community-associated UPEC isolates examined in this study exhibited either no (84%) or a weak ability (56%) to form biofilms. Similar results were reported by De Souza et al (2019), who found that community-associated UPEC strains are less able to form biofilms than hospital-acquired UPEC strains, which reportedly show stronger biofilm-forming ability. De Souza et al (2019) hypothesized that the poor ability of community-associated UPEC to form biofilms is due to low cell hydrophobicity observed in community-associated UPEC.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the substantial number of the 50 community-associated UPEC isolates examined in this study exhibited either no (84%) or a weak ability (56%) to form biofilms. Similar results were reported by De Souza et al (2019), who found that community-associated UPEC strains are less able to form biofilms than hospital-acquired UPEC strains, which reportedly show stronger biofilm-forming ability. De Souza et al (2019) hypothesized that the poor ability of community-associated UPEC to form biofilms is due to low cell hydrophobicity observed in community-associated UPEC.…”
Section: Discussionsupporting
confidence: 89%
“…The ESBL plasmid-bearing strains are often multi-drug resistant due to the combined carrying of resistance genes to aminoglycosides, quinolones, sulfonamides, and other antibiotics, which can reproduce and proliferate among the homologous and heterologous bacteria. 22,23 For severe infections caused by ESBL-producing isolates, carbapenems are often the preferred empirical therapeutic choice. Unfortunately, carbapenem-resistant Enterobacteriaceae (CRE) is globally increasing year by year and poses an urgent public health threat.…”
Section: Discussionmentioning
confidence: 99%
“…A third gene– kspMTII , belongs to a group of genes responsible for the synthesis of capsules. Gene coding capsules are most frequently found in isolates from community environments compared to hospital samples [ 83 ]. The relationship between resistance and virulence traits is mainly observed among clinical strains in the hospital environment [ 81 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%